PENGARUH KINERJA KEUANGAN DAN FIRM SIZE TERHADAP HARGA SAHAM PADA INDEX SAHAM SYARIAH - Renny Harianti; Anna Sardiana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2022)
The Islamic capital market in Indonesia continues to grow, especially in the List of Sharia Securities (DES). Each year the DES on the stock effect continues to increase in the number of issuers. In Islamic stocks there are several stock indices, one of which is the Jakarta Islamic Index (JII). The JII index has decreased and increased in the 2014-2017 period. Usually, investors will analyze before buying shares, one of them is by doing a fundamental analysis or looking at the company's financial performance, so that investors will get information about the profit opportunities that they will get. Therefore this study aims to analyze and provide empirical evidence of the effect of Net Profit Margin (NPM), Return on Equity (ROE), Earning per Share (EPS), Debt Equity Ratio (DER) and Firm Size on the stock price of companies listed in JII. The samples used in this study were 18 company stock prices with the 2014-2017 time period. Based on the results of testing using EViews 10 software, simultaneously NPM, ROE, EPS, DER, and Firm Size have a significant effect on stock prices. While partially only the ROE and EPS variables have a significant effect on stock prices. Other variables, NPM, DER, and Firm Size have no significant effect on stock prices.